Sports tourism motivation and tourist satisfaction in resort Ski tourism: A distal mediation model of tourist expectation and experience quality - Mingliang Zhang; Chen Zhang; Shuyan Li; Tao Li; Yankun Han (PLoS ONE, 2026)
The popularity of leisure skiing culture presents a paradox with declining visitor satisfaction, and this study aimed to elucidate the mechanisms influencing tourist satisfaction in leisure ski tourism through a distal mediation model. Data were collected from 302 valid samples at Changbaishan Wanda International Ski Resort within the Changbaishan National Reserve in Jilin Province, Northeast China, using mixed offline-online methods. Structural equation modeling was conducted via IBM SPSS Statistics and AMOS 26.0, utilizing maximum likelihood estimation combined with Bollen-Stine bootstrap for hypothesis testing. While direct effects confirmed all hypotheses except hypothesis 5, results further revealed significant positive mediating effects: sport tourism motivation exhibited a distal mediation effect on tourist satisfaction through tourist expectation and experience quality and an independent mediation effect through experience quality alone. These findings collectively demonstrate that tourist expectation and experience quality mediate the relationship between motivation and satisfaction in leisure skiing contexts.